Penerapan Pembelajaran Berdiferensiasi Pada Kurikulum Merdeka - Agusdianita, Neza; Dalifa; Supriatna, Irfan; Izzania, Rizqa Dwi Shofiya Maghfira; Yusnia (IPI Press, 2025)
This study explores the implementation of differentiated instruction in the Merdeka Curriculum at SDN 44 Kota Bengkulu. Teachers face significant challenges in understanding and applying differentiated teaching methods, a critical component of the Merdeka Curriculum. The research applied training and mentoring methods involving focus group discussions, classroom practices, and reflective evaluations. Data were gathered through interviews, observations, and tests to assess teachers' knowledge and students' learning outcomes. Results demonstrated that training significantly enhanced teachers' abilities to design and implement differentiated learning, leading to improved student engagement and performance. This study underscores the importance of professional development in empowering educators to adopt innovative instructional strategies effectively.